Automated Audiometry as the Screening of Hearing in Schoolchildren: Literature Review and Own Experience - Aleksandr V. Pashkov; Irina V. Naumova; Irina V. Zelenkova; Leila S. Namazova-Baranova; Elena A. Vishneva; Ksenia I. Voevodina ("Paediatrician" Publishers LLC, 2021)
In the era of healthcare digitalization, automation of some medical processes becomes extremely crucial, especially in situations where it is not possible to receive support quickly enough, for example, due to long wait for a specialist (queues) or absence of the needed specialist. This approach will help to use healthcare resources effectively. Automated audiometry is an example of automated diagnostic procedure based on algorithms and technical means for recording acoustic threshold in order to determine the hearing conditions. This review describes the process of automated hearing testing technology development in detail and several other system components (software, equipment, acoustic stimulation sources). The authors describe their own experience of using the automatic audiometry system. The results of comparative study of automated and clinical tests are presented.